Adding a Stick to the Carrot? The Interaction of Bonuses and Fines - Fehr, Ernst; Schmidt, Klaus M (American Economic Review, 2007)
Interaction in small groups is often affected by concerns for fairness and reciprocity. These effects have to be taken into account in the design of optimal incentive schemes. In Fehr and Schmidt (2004) and Fehr, Alexander Klein and Schmidt (2007, henceforce FKS) we have shown experimentally that “bonus contracts ” that rely on fairness and trust as an enforcement device can be more efficient and more profitable than “incentive contracts ” that are enforced by the courts. In the current paper we consider contracts that combine a voluntary bonus with enforceable incentive payments. The question is whether the combination of these two instruments improves efficiency or whether the use of explicit incentives undermines the functioning of implicit incentives such as voluntary bonus payments. Voluntary bonus payments are frequently used in situations where the principal and the agent both observe some aspects of the agent’s performance, but where it is impossible to contract explicitly on this information because it is not verifiable to the courts. In a one-shot relationship a purely self-interested principal would never pay the bonus and thus the agent would have no incentive to work. However, our previous experiments (FKS 2007, Fehr and Schmidt 2004) show that many principals make substantial voluntary bonus payments, even if the interaction with the